Refleksyjna praktyka w procesie stawania się nauczycielem - Bonar, Jolanta (Nauczyciel wczesnej edukacji: Rozwijanie kompetencji zawodowych, 2016)
The text attempts to analyse the process of becoming a teacher. We are purposely walking away from the notion of teachers education, which is still associated with formal academic education. Instead We talk about becoming a teacher, which has its beginning in the academic years, but is continued throughout the entire professional life. In our opinion, in this entire period the relations between elements of theory and the pedagogic practice constituting the base for reflective practice are crucial. Meetings of teachers, researchers and students creating the space of the mutual education can be their source.